MORAL VALUES AND CURRICULUM (External-Subjective and Internal-Objective in Islamic Education) - Jam'ah Abidin (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2013)
In functional, curriculum can not be separated from the two sides that is the science (thus the importance of curriculum renewal, so a curriculum designed to be changed and enhanced to absorb the latest scientific developments) and the moral and ethical values (religion). Although they are different but can not be separated. Even education as a pedagogical effort, it further strengthens the relationship between science (knowledge) and the moral and ethical values. Curriculum as a giver of a clear and definite direction in learning science should be able to realize entanglement with moral and ethical values in teaching Islamic education, in particular. Although it must be recognized that the function of praxis, the curriculum on the moral and ethical values found a difference of opinion, but the urgency of the meaning of moral and ethical values are in the curriculum , either explicitly (external) or implicit (internal), definite or conditional, there was an agreement among educators experts.